The brand identity impact of barbershop / Nur Syazwani Azlan - Azlan, Nur Syazwani (Faculty of Art and Design, 2015)
Barbershop is a place where offered haircut, groom, style and shave men's and boy's hair. There are no women in this barbershop. Barbershop is a suitable place for men's who concerned about their hairstyle and their neatness. Normally the barber (who cut the hair) will always up to date with the latest hairstyle types. In 2014, there are several types of hairstyle that was dreamed by gentlemen out there. The example of hairstyle is undercut hairstyle. This hairstyles are highly wanted by dudes. On the other hand, with the resurgence of barbering, the line up is more popular than ever and the unique spike hairstyle also is the one of cool cut for men's hairstyles nowadays. Despite the successful of an owner of barbershop, there are one more thing that the owner must know how to introduce and convince the consumer about their specialize in hairstyles. The things is "Brand Identity". Brand Identity is a set of associations that a company tries to create or maintain. These associations should reflect the values and strategy of the company. It should differentiate the company from competitors. By the impact of the brand identity itself, the barbershop will be known and will be the choice among the consumers. There are more benefits that the barbershop itself will get when the brand are popular soon.